From pixels to taxels a new world of opportunities for the blind.
Digital technologies have ever evolved at such an incredible pace. Yet, they are still leaving people behind : visually-impaired people, for example, are completely locked out from the use of touchscreen devices. An EU-funded consortium has therefore created the BlindPAD to exploit and enhance their remaining senses.